PENGGUNAAN METODE IJTIHAD INTIQAâ€™I DALAM PENGELOLAAN ZAKAT PRODUKTIF DI KOPERASI KPRI SABILULUNGAN BANDUNG: The Use of Intiqā’ī Ijtihād Method in Managing Productive Zakat at KPRI Sabilulungan Cooperative, Bandung - Risnandar, Cheppy (Asy-Syari'ah, 2017)
AbstractYusuf al-Qaradawi with his various opinions has placed him as a contemporary fiqh expert, among others in the field of zakat. His opinions include the analogy of various business activities such as bonds and stocks into trade zakat. This paper aims to explain the implementation of the trade zakat at KPRI Sabilulungan, particularly regarding the legal basis used in determining mustahiq, the istinbath method, and how to channel it. The method used in this study is descriptive analytical, which qualitatively examines the opinions of Yusuf al-Qaradawi and observations at KPRI Sabilulungan obtained by observation and interviews. The results of the study indicate that KPRI Sabilulungan uses the same legal basis as that used by Yusuf al-Qaradawi with the istinbath intiqa'i / tarjih method, especially in applying the goal of distribution of mustahik. The implementation of zakat distribution is given to amil zakat and then distributed to mustahik.Keywords:Yusuf al-Qaradhawi, zakat trade, mustahik, cooperativeÂ AbstrakYusuf al-Qaradhawi dengan berbagai pendapatnya telah menempatkannya sebagai ahli fiqh kontemporer, antara lain di bidang zakat. Pendapatnya antara lain hasil analogi berbagai kegiatan usaha seperti obligasi dan saham ke dalam zakat perdagangan. Tulisan ini bertujuan untuk memaparkan pelaksanaan zakat perdagangan tersebut di KPRI Sabilulungan, khususnya mengenai landasan hukum yang digunakan dalam penentuan mustahiq, metrode istinbath, serta cara penyalurannya. Metode yang digunakan dalam kajian ini adalah deskriptif analistis, yang secara kualitatif mengkaji pendapat Yusuf al-Qaradhawi dan hasil pengamatan di KPRI Sabilulungan yang didapat dengan cara observasi dan wawancara. Hasil kajian menunjukkan bahwa KPRI Sabilulungan menggunakan dasar hukum yang sama dengan yang digunakan oleh Yusuf al-Qaradhawi dengan metode istinbath intiqaâ€™i/tarjih, khususnya dalam penerapan sasaran pendistribusian mustahik. Adapun pelaksanaan penyaluran zakat diberikan kepada amil zakat untuk kemudian dibagikan kepada para mustahik.Kata Kunci: Yusuf al-Qaradhawi, zakat perdagangan, mustahik, koperasi